Influences of external factors in automotive sales forecasting : a portuguese case study - Blanco, Felipe Orestes Cuan Suárez (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence